Strategy for Fostering Muallaf to Islam in Improving the Practice of Islam at the Sijunjung Muallafs' House - Vuji Awaliyah; Awis Karni; Juliana Batubara (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research is motivated by the finding of converts who have not yet carried out their worship as Muslims because there is no appropriate coaching strategy. It is feared that this will have an impact on the steadfastness of converts. So a proper strategy is needed. The aim of this research is to describe and analyze: 1) Strategies used to increase the practice of Islam in the homes of Sijunjung converts, 2) Implementation of coaching strategies in increasing the practice of Islam in the homes of Sijunjung converts, 3) Supporting factors and inhibiting factors in increasing the practice of Islam at home Sijunjung convert. This research uses qualitative research methods through a descriptive approach. Data collection instruments include observation, interviews and documentation. The results of the research show that improving practice uses mentoring strategies, independent learning and tutor assistance. In implementing coaching, there are three forms of programs, namely weekly, monthly and yearly. The factor that supports the development of converts to Islam is that there is a secretariat for converts' houses. While the inhibiting factors are the lack of preachers and busy work factors.